Heart Development, Angiogenesis, and Blood-Brain Barrier Function Is Modulated by Adhesion GPCRs - Musa, Gentian; Engel, Felix; Niaudet, Colin (Handbook of experimental pharmacology, 2016)
The cardiovascular system in adult organisms forms a network of interconnected endothelial cells, supported by mural cells and displaying a high degree of hierarchy: arteries emerging from the heart ramify into arterioles and then capillaries, which return to the venous systems through venules and veins. The cardiovascular system allows blood circulation, which in turn is essential for hemostasis through gas diffusion, nutrient distribution, and cell trafficking. In this chapter, we have summarized the current knowledge on how adhesion GPCRs (aGPCRs) impact heart development, followed by their role in modulating vascular angiogenesis.
EVALuna2:25530